Vaccine effectiveness of inactivated and mRNA COVID-19 vaccine platform during Delta and Omicron wave in Jakarta, Indonesia: A test-negative case-control study. - Erlina Burhan; Farchan Azzumar; Fira Alyssa Gabriella Sinuraya; Sabarinah Prasetyo; Dwi Gayatri; Iwan Ariawan; Muhammad Ilham Dhiya Rakasiwi; Hanna Lianti Afladhia; Ahmad Fadhil Ilham; Ihya Akbar; Elvan Wiyarta (PLoS ONE)
Background Vaccination was included in the Indonesian government policy to address Delta and Omicron waves of SAR-CoV-2 infections. This study assesses the effectiveness of inactivated (CoronaVac, BBIBP-Cor) and mRNA vaccines (mRNA-1273, BNT162b2) against COVID-19 regardless of symptoms and fatal COVID-19 (mortality within 30 days after confirmed RT-PCR) during Delta and Omicron period in Jakarta, Indonesia. Methods This study case-control, test-negative study included all individuals aged over 18 years in Jakarta with complete and consistent SARS-CoV-2 RT-PCR results from 1 June to 31 August 2021 (Delta period) and 1 January to 2 April 2022 (Omicron period), as well as complete vaccination status. This study integrates several public health data from the Jakarta provincial government. From the odds ratio, vaccine effectiveness (VE) was analyzed as the primary outcome using unmatched analysis, matched analysis, and adjustments for other factors. Results This study includes 982,885 eligible subjects recorded from March 2021 to April 2022. All subjects generally underwent testing 4-9 weeks after their last vaccine dose. The VE of 2-dose inactivated vaccine against SARS-CoV-2 infection during Delta wave was 22.06% (95% CI 20.63-24.54) and the VE against fatal COVID-19 was 78.55% (95% CI 72.91-83.00). A complete primary dose of mRNA vaccine showed VE of 24.81% (95% CI 16.81-32.09) against infection during Omicron wave. Furthermore an additional mRNA booster dose showed VE of 68.82% (95% CI 54.11-78.82) based on unmatched analysis. Conclusion A complete primary dose of inactivated vaccine provided mild protection against COVID-19 and essential protection against fatal cases during the Delta wave, but offered little to no protection during the Omicron wave. In contrast, the mRNA vaccine, either as primary vaccination, homologous, or heterologous booster regimen, conferred acceptable protection against Omicron. This study recommends real-world vaccination strategies for LMICs with typical vaccine supply constraints.